VOCATIONAL HIGH SCHOOL TEACHERS’ LEVELS OF BELIEF IN EDUCATION AND MOTIVATION TO TEACH - Türkan ARGON (Fırat University, 2019)
In this study teachers’ levels of belief in education and their opinions about motivation to teach were determined, the relation between their opinions were examined and it was determined that teachers’ personal variables whether create or not meaningful differences for their opinions. The sample of the study consists of 185 teachers who work at vocational high schools in Bolu in 2016-2017 education year. Research data were collected via Teachers’ Levels of Believe in Education Scale (TLBES) and Motivation to Teach Scale. Non-parametric analyses were used as research data did not show normal distribution. According to research results teachers’ level of belief in education is at “don’t agree” level and their motivation to teach level is “indecisive”. Teachers’ gender variable didn’t create any meaningful difference at their levels of belief in education and motivation to teach. Branch variable created meaningful difference in favor of culture teachers at multi-faceted development dimension of TLBES. The variable of educational background created meaningful difference in favor of teachers who have bachelor’s degree at internal motivation sub dimension and total of motivation to teach; at socialization and preparing to upper-education dimensions and total of TLBES. Choosing teachership voluntarily created meaningful difference in favor of teachers who chose the profession willingly at total of motivation to teach scale and sub dimensions; socialization dimension of TLBES. School type variable created meaningful difference at total of motivation to teach scale and internal motivation dimension; and multi-faceted development dimension of TLBES. There is a positive meaningful relation between teachers’ opinions about their belief in education and motivation to teach at medium level. According to research results such kind of suggestions were stated: the reasons of why teachers’ level of motivation to teach and belief in education is not enough should be examined and necessary precautions should be taken; graduate tracking system should be developed to increase teachers’ belief in education; successful senior teachers should mentor the teachers who haven’t chosen their profession willingly so that they can understand the importance and pleasure of teaching profession